التهرب الضريبي واثره على التنمية الاقتصادية في العراق (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Highlights the role of taxes in being a major source of funding sources internal economic and social development, and then, any decrease in tax revenue caused by tax evasion, for example, would weaken the government's ability to finance their investments and core financing private sector investment as a result of reduced ability to increase their reserves's cash banks, as well as the weakening of the effectiveness of tax evasion taxes as a tool to guide economic activity in the framework of service for development, and to achieve justice. And the statement of the reasons for and methods of evasion mandated to pay the tax due on them, whether legitimately or illegal with the statement of the proposed methods to tackle tax evasion and eliminate it. Also suffer GCT of the problem of non-payment of tax owed by the taxpayer through the followers of various styles legitimate third parties. And that there are several factors that lead to continued which this leads to reduced tax revenues and therefore did not achieve the goals of economic development. And reduce the phenomenon of tax evasion is working to increase tax revenue and thus reflected positively on economic development. One of the most important conclusions reached by the research show that high tax evasion phenomenon negatively affects economic development projects and thus the loss in state revenue. And the success of the economic development process need to many resources to achieve such as taxes, fees, and revenues of state property, loans, and deficit financing. The most important recommendations reached by the research, the need to give full flexibility to run the Iraqi mechanics of the tax system in terms of increased state revenues in order to achieve economic and social development required. And the need to raise awareness of the tax being one of the fundamental means to combat evasion and the success of the process of economic development, and feeling designate that the contribution to pay the tax contribute to building the economic development process